Salmonella typhi abscess as a late complication of simple cyst of the liver: A case report - İsmail GÖMCELİ and Ahmet GÜRER and Mehmet ÖZDOĞAN and Nuraydın ÖZLEM and Raci AYDIN (Turkish Journal of Gastroenterology, 2019)
-